36‐2: Invited Paper: The Latest Breakthrough of Printing Technology for Next Generation Premium TV. Issue 1 (25th September 2020) - Lee, Jueng Gil(James); Yu, Lei; Zhuang, Jinyong; Li, Zhe; Chen, Yawen; Dong, Ting; Sun, Xianwen; Yao, Songjin; Xie, Xiangwei; Fu, Dong; Yan, Xiaolin
Abstract : The ink jet printing RGB patterning technology ("Printing Technology") for OLED TV application is gathering momentum toward commercialization. The main technical challenges of printing technology, are (1) to improve the OLED TV panel performance fabricated by printing technology, and (2) to establish manufacturable the G8.5/G11 MURA‐Free printing technology. Recently, the printing technology has made tremendous progress in terms of OLED material performance( life time, current efficiency, color gamut and driving voltage) including optimization of top emission device architecture and maturity of MURA‐Free ink‐jet printing technology, such as high performance ink‐jet printing equipment equipped with excellent print‐head in terms of drop volume uniformity and drop placement accuracy, ink formulation for reliable jetting, hydrophobic bank material/design/process and unique vacuum dry & bake process. TCL Group (Guangdong Juhua Printed Display Technology, TCL Corporate Research, TCL CSOT) has been developing the manufacturable printing technology for TV application and innovative flexible display technology since 2015. Based on development activities of 31" 4K OLED TV, 31" 4K H‐QLED TV(World 1 st Demo at CES 2019), 31" FHD Flexible Printed OLED TV and 4.92" (403ppi) high resolution panel, the latest breakthrough of printing technology for next generation premium TV is discussed in details.